2010
DOI: 10.1097/mao.0b013e3181cdd8b7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 629 Vestibular Schwannomas According to Preoperative Caloric Responses

Abstract: Our results suggest that caloric responses are well correlated with the studied preoperative and intraoperative factors and provide predictive factors with regard to postoperative facial palsy and hearing outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
3
12
4
1
Order By: Relevance
“…Previous histopathological studies have shown that >80% of the ganglions have to be lost before a shift in PTA threshold occurs, and that the loss of ganglions affects discrimination and PTA disproportionally [29] . Contrary to our results, other studies have shown a correlation between caloric hypofunction and size [5,11,21] . An explanation for the missing correlation in our study could be the relatively small size interval of tumors of which 91% had a diameter of 11-30 mm.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous histopathological studies have shown that >80% of the ganglions have to be lost before a shift in PTA threshold occurs, and that the loss of ganglions affects discrimination and PTA disproportionally [29] . Contrary to our results, other studies have shown a correlation between caloric hypofunction and size [5,11,21] . An explanation for the missing correlation in our study could be the relatively small size interval of tumors of which 91% had a diameter of 11-30 mm.…”
Section: Discussioncontrasting
confidence: 99%
“…Almost all patients (98%) had a lesioned side caloric hypofunction. The mean UW of 72% corresponds to a severe hypofunction according to a previous classification [11] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, with increasing size the vHIT might become pathological [69][70][71]. It is controversially discussed if UW is a predictor for tumour size [70,72] or not [73]. It was shown that the VOR gain of vHIT is not correlated with the tumour size [70] but rated together with the CI there was a correlation.…”
Section: Vestibular Schwannoma (Vs)mentioning
confidence: 99%
“…Nuestra asociación entre prueba calórica asimétrica, >25% y un v-HIT alterado, fue de 77,7%, mayor a lo que otros autores han reportado en neuronitis vestibular (33%) 19 . En nuestro estudio el tamaño del tumor no se correlacionó con mayor alteración del v-HIT así como tampoco con mayor asimetría de la prueba calórica como ha sido descrito en otros trabajos 20 . Esto puede ser explicado por el lento crecimiento del schwanoma con deterioro crónico del sistema vestibular lo que produce una compensación vestibular a nivel central generando niveles de ganancias bajas (menores a 1) en ambos lados.…”
Section: Discussionunclassified